Geomorphological and depositional features around Thulagi Glacial Lake in Manaslu Himal, central Nepal - Volk, Hellmut (Journal of Nepal Geological Society, 1998)
Several glaciers in the Higher Himalaya of Nepal show a high rate of ablation resulting in their recession and thereby giving rise to large glacial lakes on the site of former glacier tongues. The Thulagi Glacier at the southwestern foot of the Manaslu Peak (8156 m) represents one of those quickly shrinking valley glaciers whose ice tongue has been converted into a large lake of 2 km length at an elevation of 3960 m. No till fabric occurs in the inner moraine ridges that surround and dam the lake. As these moraine deposits lack fine constituents as silt and clay, exhibit stratification as well as tilted layers, and are composed of subrounded pebbles, it is concluded that these moraine ridges represent push moraines having originated from kame terraces. A low hummocky terrain inside the high terminal push moraine at the downstream end of the lake is interpreted as a younger ice-cored push moraine still being in a collapsing state. The Thulagi Glacier appears to have oscillated in length and volume several times in the late Pleistocene and Holocene earth history.